2021
DOI: 10.1038/s41393-021-00613-9
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of dopamine infusion on lipid and cytokine concentrations in persons with a cervical spinal cord injury—a pilot study

Abstract: Study design Acute experimental studyObjectives To investigate the acute response of markers of lipid metabolism and interleukin (IL)-6 to dopamine infusion in people with a cervical spinal cord in injury (CSCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In keeping with the FFA response, there was no difference in the acute increase in ketone body concentration between SCI C and AB. This is in line with Hoekstra et al [23], who found a similar increase in total ketone body concentration in persons with SCI C and AB individuals following dopamine infusion. The lack of difference between both groups in the present study may be partly explained by the similar increase in FFA concentration, as FFA act as a substrate for ketone bodies [15].…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with the FFA response, there was no difference in the acute increase in ketone body concentration between SCI C and AB. This is in line with Hoekstra et al [23], who found a similar increase in total ketone body concentration in persons with SCI C and AB individuals following dopamine infusion. The lack of difference between both groups in the present study may be partly explained by the similar increase in FFA concentration, as FFA act as a substrate for ketone bodies [15].…”
Section: Discussionsupporting
confidence: 92%